2011
DOI: 10.1111/j.1532-5415.2011.03662.x
|View full text |Cite
|
Sign up to set email alerts
|

Belt Restraint Reduction in Nursing Homes: Effects of a Multicomponent Intervention Program

Abstract: A multicomponent intervention program led to a substantial reduction in use of belts, full-enclosure bedrails, and sleep suits without increasing the use of other physical restraints, psychoactive drugs, or falls and fall-related injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 38 publications
2
74
0
2
Order By: Relevance
“…Not using belt restraints did not lead to any adverse effects such as an increase in psychoactive drug use, falls or fall-related injuries. These results are in line with the effects of the EXBELT intervention in the larger study among already admitted residents (Gulpers et al, 2011). That study also showed that a statistically significant decrease in the use of belts and other physical restraints in nursing homes is attainable without causing an increase in psychoactive drug use, falls or fall-related injuries (Gulpers et al, 2011).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Not using belt restraints did not lead to any adverse effects such as an increase in psychoactive drug use, falls or fall-related injuries. These results are in line with the effects of the EXBELT intervention in the larger study among already admitted residents (Gulpers et al, 2011). That study also showed that a statistically significant decrease in the use of belts and other physical restraints in nursing homes is attainable without causing an increase in psychoactive drug use, falls or fall-related injuries (Gulpers et al, 2011).…”
Section: Discussionsupporting
confidence: 75%
“…The strategy includes a policy change, education, consultation and the availability of alternative interventions. The implementation of the EXBELT intervention resulted in a 50% reduction in belt use (odds ratio = 0.48, 95% confidence interval = 0.28-0.81; p = .005) (Gulpers et al, 2011). The aim of the present study was to examine the effect of EXBELT intervention on the prevention of belt restraint use in newly admitted residents of psychogeriatric nursing home wards.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies also detected a lack of awareness of the potential complications [34, 36, 40], so that staff may erroneously overestimate the benefits of these devices. Teaching programs addressing these issues, supported by other measures, such as the implementation of technical assistance, changes in institutional culture, or support from a specialist consultant, have been found effective in reducing their usage [16, 41, 42]. …”
Section: Discussionmentioning
confidence: 99%
“…En total en El Puig se pierde un 40% de la población y en Conarda un 37%. Estos porcentajes son similares a las pérdidas por exitus en estudios de similar naturaleza en otros países [17][18] .…”
Section: Aquí Poner Figuraunclassified